Blockchain trading mechanism based on attached chain for the delay tolerant network - Lingling ZI; Xin CONG (Tongxin xuebao)
In order to deploy a blockchain on the non-continuous connectivity delay tolerant network,a blockchain trading mechanism was designed,which could run on this type of network.First,the identifier was introduced into the existing block structure and a block structure on the attached chain was presented,which could append the blocks generated during network disconnection.Then,the approaches including the block package,block mining and block consensus on the attached chain were proposed.Finally,a confirming consensus approach was presented to avoid block fraud in the process of appending the attached chain.Through theoretical proof and experimental analysis,the proposed mechanism can support blockchain trading in the delay tolerant network.